Analisis Peran Literasi Keuangan, Perilaku Keuangan Serta Financial Technology Dalam Meningkatkan Kinerja Keuangan UMKM (Survei pada Pedagang Pasar Jungke Karanganyar) - Mawarni Butar Butar; Dorothea Ririn Indriastuti (CV. ITTC INDONESIA, 2026)
This study explores the contribution of financial literacy, financial behavior, and financial technology to the financial performance of MSMEs among traders at Jungke Market, Karanganyar. Using a quantitative methodology, data were collected through questionnaires from 90 respondents selected using proportional cluster random sampling. Through multiple linear regression analysis, it was found that all three independent variables have significance values below 0.05, indicating a positive and significant effect on financial performance partially (t-test). The coefficient of determination (R²) of 52.3% shows that these variables are able to explain the variation in financial performance, while the remaining percentage is influenced by external factors. This study concludes that strengthening financial literacy, financial behavior, and financial technology is a key factor in improving the financial performance of business actors.